The great balancing act - The art of performance analysis in academy soccer in England - Hounsell, T.; Oxenham, P.; Mulvenna, C. (Sport Performance & Science Reports, 2021)
The increasing availability of performance analysis (PA) in soccer has led to players being subjected to more analysis than before (1). With a greater number of analysts being em ployed across age groups and participation levels (2, 20), PA appears here to stay as a feature of elite player development and the multidisciplinary sport science teams aiding coaches within their roles (3, 4). Yet given the financial gain that an academy player could bring a football club (5) and the complexities of the role of a coach in academy soccer the way in which PA is used is complex and multifaceted. It has been ac- knowledged that coaches within elite youth soccer lack expert knowledge around the implementation of PA (21), therefore highlighting the importance of analyst employment to support the coaching process. Aim of the paper - Identify the way in which PA is used within elite academy soccer to support match preparation. - Critically analyse the role of the analyst to aid the development of soccer players.